Course of cannabis use and clinical outcome in patients with non-affective psychosis: a 3-year follow-up study. Issue 9 (5th February 2015) - van der Meer, F. J.; Velthorst, E.; ,
Abstract : Background: Prospective studies on the relationship between course of cannabis use and clinical outcome in patients with non-affective psychotic disorders are inconclusive. The current study examined whether (1) persistent, recently started, discontinued and non-cannabis-using patients with a psychotic disorder differed with regard to illness outcome at 3-year follow-up, and (2) whether timing of cannabis discontinuation was associated with course of clinical outcome. Method: This 3-year follow-up study was part of a multi-center study in the Netherlands and Belgium (Genetic Risk and Outcome of Psychosis; GROUP). We used mixed-model analyses to investigate the association between pattern of cannabis use and symptoms, global functioning and psychotic relapse. Results: In our sample of 678 patients, we found persistent users to have more positive and general symptoms, worse global functioning and more psychotic relapses compared with non-users and discontinued users [Positive and Negative Syndrome Scale (PANSS) positive, p < 0.001; PANSS general, p < 0.001; Global Assessment of Functioning (GAF) symptoms, p = 0.017; GAF disability, p < 0.001; relapses, p = 0.038]. Patients who started using cannabis after study onset were characterized by worse functioning at baseline and showed an increase in general symptoms (including depression and anxiety) at the 3-year follow-up ( p = 0.005). Timing of cannabis discontinuation was not associated with clinical outcome. Conclusions: These findings suggest that cannabis use in patients with a psychotic disorder has a long-lasting negative effect on illness outcome, particularly when persistent. Treatment should focus on discouraging cannabis use.